Question

Solve the equation.

(2x^3+xy)dx+(x^3y^3-x^2)dy=0

give answer in form F(x,y)=c

Answer #1

Use the method for solving homogeneous equations to solve the
following differential equation.
(9x^2-y^2)dx+(xy-x^3y^-1)dy=0
solution is F(x,y)=C, Where C= ?

Consider the following differential equation: dy/dx =
−(3xy+y^2)/x^2+xy
(a) Rewrite this equation into the form M(x, y)dx + N(x, y)dy =
0. Determine if this equation is exact;
(b) Multiply x on both sides of the equation, is the new
equation exact?
(c) Solve the equation based on Part (a) and Part (b).

Solve:
(2x^2 - y) dx + (x + y^2) dy = 0

solve differential equation ((x)2 - xy +(y)2)dx - xydy
= 0
solve differential equation (x^2-xy+y^2)dx - xydy =
0

solve the bernqoulli equation dy/dx+xy+xy^2=0

solve for y:
1. dy/dx= xe^y separable
2. x(dy/dx)+3y=x^2 when y(5)=0 1st order linear

Solve the Homogeneous differential equation
(7 y^2 + 1 xy)dx - 1 x^2 dy = 0
(a) A one-parameter family of solution of the equation is y(x)
=
(b) The particular solution of the equation subject to the
initial condition y(1) =1/7.

Determine the type of below equations and solve it.
a-)(sin(xy)+xycos(xy)+2x)dx+(x2cos(xy)+2y)dy=0
b-)(t-a)(t-b)y’-(y-c)=0 a,b,c are
constant.

Solve the differential equation (5x^4 y^2+ 2xe^y - 2x cos (x^2)) dx
+ (2x^5y + x^2 e^y) dy = 0.

Solve the following equation using integrating factor.
y dx + (2x − ye^y) dy = 0

ADVERTISEMENT

Get Answers For Free

Most questions answered within 1 hours.

ADVERTISEMENT

asked 1 minute ago

asked 2 minutes ago

asked 12 minutes ago

asked 12 minutes ago

asked 16 minutes ago

asked 23 minutes ago

asked 25 minutes ago

asked 32 minutes ago

asked 32 minutes ago

asked 32 minutes ago

asked 33 minutes ago

asked 38 minutes ago